2021
DOI: 10.3389/fneur.2021.642645
|View full text |Cite
|
Sign up to set email alerts
|

Ictal and Interictal Cardiac Manifestations in Epilepsy. A Review of Their Relation With an Altered Central Control of Autonomic Functions and With the Risk of SUDEP

Abstract: There is a complex interrelation between epilepsy and cardiac pathology, with both acute and long-term effects of seizures on the regulation of the cardiac rhythm and on the heart functioning. A specific issue is the potential relation between these cardiac manifestations and the risk of Sudden and Unexpected Death in Epilepsy (SUDEP), with unclear respective role of centrally-control ictal changes, long-term epilepsy-related dysregulation of the neurovegetative control and direct effects on the heart function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 110 publications
0
13
0
Order By: Relevance
“…Experimental studies demonstrated that brain lesions in some autonomic regulatory regions prevent immune activation depending on T-cell response [33][34], supporting that parasympathetic and sympathetic drives mediate immune adaptative responses. Ictal and interictal autonomic disturbances can occur in PWE with a possible impact on immune response [35][36][37][38]. Moreover, some data suggest that ASM can directly affect both humoral and cellular immunity, modifying the synthesis and expression of cytokines [12], but the mechanisms are not fully understood and other intercurrent factors may act as confounders.…”
Section: Immune Response In Pwementioning
confidence: 99%
“…Experimental studies demonstrated that brain lesions in some autonomic regulatory regions prevent immune activation depending on T-cell response [33][34], supporting that parasympathetic and sympathetic drives mediate immune adaptative responses. Ictal and interictal autonomic disturbances can occur in PWE with a possible impact on immune response [35][36][37][38]. Moreover, some data suggest that ASM can directly affect both humoral and cellular immunity, modifying the synthesis and expression of cytokines [12], but the mechanisms are not fully understood and other intercurrent factors may act as confounders.…”
Section: Immune Response In Pwementioning
confidence: 99%
“…The reason for this effort is that the unexplained sudden death in epilepsy (SUDEP) risk, as demonstrated by autopsy and clinical studies, is 0.7-1.3/1000, which is 24 times higher than the normal population, especially in case of idiopathic and cryptogenic epilepsy [21]. Electrical stimulation of different locations within the brain was found to induce dysrhythmia such as tachyarrhythmia, bradyarrhythmia (time to time), asystole (rarely), AV block, and ventricular fibrillation [9,22,23]. Seizures affecting the temporal lobe, insular cortex, and amygdala tend to cause dysrhythmia more frequently [24].…”
Section: Discussionmentioning
confidence: 99%
“…Although these events are related primarily to postictal brainstem dysfunction, it has been suggested that the involvement by the epileptic discharges of cortical areas that participate in breathing and vegetative regulation may also pay a role 62 . Amygdala, peri‐sylvian cortex, including the insula, and the anterior/middle cingulate gyrus are the main cortical nodes of the central autonomic networks, involved in regulation of breathing, cardiac rhythm, and blood pressure 62–64 . Structural and functional magnetic resonance imaging (MRI) studies identified changes in these regions in patients who died from SUDEP and individuals at high risk of SUDEP 65–67 .…”
Section: Factors Potentially Associated With Reduction Of Mortality A...mentioning
confidence: 99%